Radiolytic Stability of the TEHDGA-Impregnated Silica-Based Adsorbent for Extraction Chromatography - Miyazaki Yasunori; Sano Yuichi; Ishigami Ryoya (EPJ Web of Conferences)
Gamma-ray and He2+ ion beam (which is simulating alpha-ray from Am-241, for example) were applied to the TEHDGA adsorbent to evaluate hydrogen gas production, leaching of organics by 3 M HNO3 solution, thermal characteristics and speciation of degradation products. These elements were brought together to assess the stability of the adsorbent after a run of MA separation from an irradiating raffinate of 1 kGy/h dose rate.